The IZA Evaluation Dataset Survey: A Scientific Use File - Patrick Arni; Marco Caliendo; Steffen Künn; Klaus F. Zimmermann (Institute for the Study of Labor (IZA), 2014)
This reference paper describes the sampling and contents of the IZA Evaluation Dataset Survey and outlines its vast potential for research in labor economics. The data have been part of a unique IZA project to connect administrative data from the German Federal Employment Agency with innovative survey data to study the out-mobility of individuals to work. This study makes the survey available to the research community as a Scientific Use File by explaining the development, structure, and access to the data. Furthermore, it also summarizes previous findings with the survey data.
Keywords: C81; H43; J68; 330; survey data; scientific use file; labor market policies; evaluation; migration; ethnicity; attitudes; behavior; skills